Unpacking implementation capacity and contexts for degree reclamation strategies: What factors move the equity needle? - Taylor, Jason; Rubin, Paul; Kauppila, Sheena; Davis, Leanne (Education Policy Analysis Archives, 2021)
This paper used data from a multi-institutional study of community colleges developing and implementing degree reclamation strategies (adult reengagement and reverse credit transfer) to understand and unpack the factors that influence implementation and capacity development. The data come from seven colleges that are implementing equity-focused degree reclamation strategies aimed to reduce the population of “some college, no degree.” The research team used an interdisciplinary lens to identify these factors drawing from literature on capacity-building. Prior to the start of implementation, researchers surveyed institutions and institutional stakeholders to assess baseline capacity, and they tracked institutional participation and engagement in the strategy development and implementation process. This paper highlights findings from this research to identify which factors are most related to implementation variation and strategy outcomes.